Being Religious Character Through Extracurricular Tahfiz al-Qur’an - Nur Fadhilah; Dedi Masri; M. Inggit Prabowo; Bunga Alfi Syahria (Sufiya Journal of Islamic Studies, 2023)
The purpose of this study is to explain how the stages of forming the religious character of students with the Tahfiz al-Quran extracurricular activities at Mas Al-Furqon Kualuh are to identify the Islamic character of students at MAS Al-Furqon Kualuh through Tahfiz. This research method belongs to the qualitative type. The researcher conducted interviews with teachers who teach at MAS Al-Furqon Kualuh, observation, and documentation through one of the teachers and students at MAS Al-Furqon. The researcher also descriptively presented the data by determining interview guidelines and then extracting data from related books and journals using basic studies and analyses supporting the data. The research problem formulation includes the character-building process in students at MAS Al-Furqon Kualuh? What is the relationship between religious character and Tahfiz al-Qur’an? How is the implementation of character education for students through Tahfiz al-Qur’an at MAS Al-Furqon Kualuh?